MENUMBUHKAN KETERAMPILAN BERPIKIR KRITIS SISWA SD MELALUI PENERAPAN PEMBELAJARAN TEMATIK - Munawaroh, Isniatun (MAJALAH ILMIAH PEMBELAJARAN, 2009)
Cultivate skills think critical since the age of the Primary School is really enabled, considering skills to think about being when humankind is born. These skills can be provided in education especially in the process pembelajaran take place. One of the models pembelajaran that can be integrated to cultivate skills think critical in the Primary School am pembelajaran thematic. Lerning thematic is learning pack the material, learning him in the form of the theme and the flexible in his implementation. Meaning that giving the opportunity to use heterogenous the method and the media that are aimed to activate the student in studying. Learning thematic that is aimed to cultivate skills think critical am by using the discussions strategy and consultations, the child teaches the child or peer teachin, the show and direct sample, the exercise is led and the free.